Analisis Hubungan Perilaku Perlindungan Sinar Matahari dan Faktor Internal Terhadap Kejadian Acne Vulgaris Pada Remaja SMPN 1 Jatinangor - Nailah Ibtisamah; Nunung Siti Sukaesih; Imam Tri Sutrisno (Universitas Galuh, 2026)
Acne is a common skin problem among adolescents and can affect both self-confidence and skin health. One external factor suspected to play a role in acne development is sun protection behavior, which includes the use of sunscreen, protective clothing, and habits to avoid direct sun exposure. This study aimed to examine the relationship between sun protection behavior and the incidence of acne vulgaris among junior high school students in Jatinangor. A quantitative approach with an analytical correlational cross-sectional design was employed. The study was conducted at SMPN 1 Jatinangor in 2025, involving 295 students selected through stratified random sampling. Research instruments included the Sun Protection Behavior Scale (SPBS) questionnaire and the Global Acne Grading System (GAGS) questionnaire. Data were analyzed using Spearman’s correlation test. The results showed that most students had a high level of sun protection behavior and experienced mild acne. Spearman’s test yielded r = −0.065 and p = 0.265, indicating no significant relationship between sun protection behavior and the incidence of acne vulgaris. It can be concluded that acne occurrence is more influenced by internal factors, such as hormonal changes and facial hygiene, than by external factors like sun exposure. Continuous education on skin care is necessary to increase adolescents’ awareness of maintaining skin health from an early age.